Incidence, risk factors, and prognosis of abnormal liver biochemical tests in COVID-19 patients: a systematic review and meta-analysis - Wu, Yanyan; Li, Hongyu; Guo, Xiaozhong; Yoshida, Eric M.; Mendez-Sanchez, Nahum; Levi Sandri, Giovanni Battista; Teschke, Rolf; Romeiro, Fernando Gomes [UNESP]; Shukla, Akash; Qi, Xingshun (Springer Nature, 2020)
Background and aims: Coronavirus disease 2019 (COVID-19) pandemic is ongoing. Except for lung injury, it is possible that COVID-19 patients develop liver injury. Thus, we conducted a systematic review and meta-analysis to explore the incidence, risk factors, and prognosis of abnormal liver biochemical tests in COVID-19 patients. Methods: PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), VIP, and Wanfang databases were searched. The incidence of abnormal liver biochemical tests, including aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), gamma-glutamyl transpeptidase (GGT), total bilirubin (TBIL), and albumin (ALB), was pooled. Risk ratio (RR) was calculated to explore the association of abnormal liver biochemical tests with severity and prognosis of COVID-19 patients. Results: Forty-five studies were included. The pooled incidence of any abnormal liver biochemical indicator at admission and during hospitalization was 27.2% and 36%, respectively. Among the abnormal liver biochemical indicators observed at admission, abnormal ALB was the most common, followed by GGT, AST, ALT, TBIL, and ALP (39.8%, 35.8%, 21.8%, 20.4%, 8.8%, and 4.7%). Among the abnormal liver biochemical indicators observed during hospitalization, abnormal ALT was more common than AST and TBIL (38.4%, 28.1%, and 23.2%). Severe and/or critical patients had a significantly higher pooled incidence of abnormal liver biochemical indicators at admission than mild and/or moderate patients. Non-survivors had a significantly higher incidence of abnormal liver biochemical indicators than survivors (RR = 1.34, p = 0.04). Conclusions: Abnormal liver biochemical tests are common in COVID-19 patients. Liver biochemical indicators are closely related to the severity and prognosis of COVID-19 patients.
Keywords: COVID-19; Hepatic; Incidence; Liver; Risk; SARS-CoV-2